Association Between Harsh Disciplinary Methods and Child Functioning in Children Aged 7–14 Years in Punjab, Pakistan - Kamran, Zaibunnisa (Journal of interpersonal violence, 2024)
Despite having adverse physical and mental health outcomes, harsh disciplinary methods are commonly practiced all over the world. This study aims to measure the harsh disciplinary actions taken by parents and their association with child functioning in children, aged 7 to 14 years in Punjab, Pakistan. This study is based on secondary data obtained from the United Nations Children’s Fund (UNICEF’s) Multiple Indicator Cluster Survey, conducted in the Punjab province from 2017 to 2018. Parents/caregivers of 19,721 children were included in the analysis. Questionnaire-based interviews were conducted, and the data collection form included sociodemographic information, questions on different “Methods of Child Discipline” and the “Child functioning module.” The data was analyzed using STATA 15.0. Multiple logistic regression analysis was conducted to calculate the adjusted odds ratio and 95% CI exploring the association between harsh disciplinary methods and child functioning. More than 50% of children were exposed to severe physical, psychological, and emotional disciplinary methods. Exposure to severe physical aggression was associated with increased difficulty in learning (2.60 [1.27, 5.31]), remembering (2.83 [1.47, 5.44]), controlling behavior (1.63 [1.21, 2.18]), anxiety (1.98 [1.25, 3.13]), depression (2.57 [1.57, 4.22]) and making friends (1.94 [1.01, 3.79]). Whereas moderate physical aggression and psychological aggression were associated with (1.48 [1.19, 1.84]) and 1.5 times (1.20, 1.84) increase in difficulty in controlling behavior, respectively. Nonviolent actions were associated with protective odds for self-care (0.33 [0.17, 0.65]), communication (0.51 [0.27, 0.96]), learning (0.56 [0.33, 0.95]), remembering (0.62 [0.39, 0.90]), concentration (0.50 [0.31, 0.80]), anxiety (0.60 [0.46, 0.79]) and depression (0.67 [0.49, 0.92]). Severe disciplinary methods are detrimental to the child’s personal care, mental, social, emotional, and psychological well-being, whereas nonviolent actions are associated with positive child functioning. In a third-world country such as Pakistan, this topic is widely undiscovered and understudied, thus emphasizing the need for awareness and education of parents and healthcare providers.